A DECONSTRUCTION OF CHARACTERS IN â€œSPONGEBOB MOVIE: SPONGE ON THE RUNâ€ - Eno Nur Hasanah; Norma Ita Solichah (IAI Al-Qolam, 2022)
This research discussed the deconstruction of characters, which aimed to deconstruct a binary opposition between the main character and minor character in SpongeBob Movie: Sponge on the Run. The researcher used note taking as an instrument to get the valid data. Primary data in this study was taken from the dialogue of the characters in the